THE DISCOURSE OF THE QUILOMBOLAS OF THE SERTÃO DAS GERAIS - Peixoto, Ana Cristina Santos (Seven Editora, 2025)
This article describes the discursive manifestations uttered by members of quilombola communities, understood in this research as traditional communities whose members are now recognized as descendants of enslaved blacks. We investigated the discourses of the quilombola members that revealed the constitution of identities, specifically, of the Orion camp belonging to the Territory of Brejo dos Crioulos. We based the investigation on the Theory of Analysis of the French Discourse, and the analysis of the data confirmed that there are several identities that constitute the narratives investigated.DOI: https://doi.org/10.56238/sevened2025.018-016 [1] This text is part of Peixoto's Doctoral Thesis (2014) entitled: The construction of identities in narratives of quilombola communities in the sertão das gerais. From this thesis and the Território de Brejo dos Crioulos we also have a book chapter in the work Educational Sciences: Perspectives and Interdisciplinary Practices - 2025 from Editora Seven.